PENGARUH FASILITAS DAN KENYAMANAN TERHADAP KEPUASAN PENGUNJUNG SOLO TECHNOPARK SEBAGAI RUANG PUBLIK DI KOTA SURAKARTA - Amelia Zahra Fatika; Augustin Rina Herawati (Journal of Management and Public Policy, 2026)
As a livable city, Surakarta is committed to providing adequate public spaces for its citizens. However, the current realization of public Green Open Space (RTH) has only reached 4.69%, falling significantly short of the 20% minimum standard mandated by Law No. 26 of 2007. The City Government designated Solo Technopark as a priority public infrastructure project under Mayoral Regulation No. 33 of 2023. The development of Solo Technopark aims not only to expand green spaces but also to provide a hub for the creative economy, arts, and socio-cultural activities. Given its strategic role, evaluating visitor satisfaction at Solo Technopark is essential to ensure the effectiveness of its functions and its overall impact on the community. This study aims to analyze the influence of Facilities (X1) and Comfort (X2) on Visitor Satisfaction (Y) in Solo Technopark’s public space. A quantitative explanatory approach was employed, with data collected through interviews, documentation, and questionnaires distributed to 95 respondents using a simple random sampling technique. The results indicate that Facilities (X1) and Comfort (X2) partially have a positive and significant effect on Visitor Satisfaction (Y). Simultaneously, both independent variables also show a significant positive influence on Visitor Satisfaction (Y). Solo Technopark management is advised to optimize digital services, standardize infrastructure and navigation, and engage in creative community collaborations to improve the visitor experience.